Faith and Protest - Leila Hassim (African Journal of Gender and Religion (AJGR))
This article considers the application of two counter-cultural issues of faith taken from a thirteenth century French manuscript to current issues of faith in South Africa. The thirteenth century French manuscript is a mystical treatise by Marguerite Porete who was burned at the stake for her ideas of faith, and the current issue of faith in South Africa is the charismatic movement currently flourishing on the South African landscape.